Russia in the Baltic states’ foreign policy in 1990s: conceptual analysis - Valodzkin, Andrei A. (Journal of the Belarusian State University. International Relations, 2019)
The goal of the article is to examine, how the main principles and concepts of the Baltic states’ foreign policy shaped their relations with Russia in 1990s. For this purpose it analyzes the reasons standing behind each of these principles and concepts and reveals their implications on Baltic foreign policy towards Russia. Besides the author applies some theoretical approaches, explaining the behavior of small states on the international arena, to reveal the mechanisms of forming the major trends of Baltic foreign policies in the 1990s and their perceptions of Russia.
Keywords: foreign policy; Baltic states; Latvia; Lithuania; Estonia; Russia